Charlie and the great glass elevator : the further adventures of Charlie Bucket and Willy Wonka, chocolate-maker extraordinary - Dahl, Roald, 1916-1990; Schindelman, Joseph (New York : Bantam Books, 1979)
Taking up where Charlie and the Chocolate Factory leaves off, Charlie, his family, and Mr. Wonka find themselves launched into space in the great glass elevator.
Keywords: Humorous stories; Outer space -- Fiction; Science fiction